2020
DOI: 10.1097/mpg.0000000000002707
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Manifestations Are Associated With Disease Severity in Pediatric Onset Inflammatory Bowel Disease

Abstract: Objectives: The aim of this study was to investigate a possible association between extraintestinal manifestations (EIM) and a more severe disease course in pediatric onset inflammatory bowel disease (pIBD). Methods: This study compares the disease course of pIBD patients (IBD diagnosis <15 years of age) with and without EIM in a population-based cohort from Denmark. Patients diagnosed with pIBD between 1998 and 2008 were included in the study and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…Interestingly, EIMs at diagnosis have been also associated with a more severe course over time [ 17 ]. Similar results have been reported for pediatric-onset CD [ 18 ], suggesting that EIMs in children may have a worse prognosis than in adults and predict a more progressive disease course [ 15 , 19 , 20 ]. Aside from the younger age, the extension of disease and the degree of intestinal inflammation also seem to be associated with the risk of development of one or more EIMs [ 21 , 22 ].…”
Section: Extraintestinal Manifestations Of Ibdssupporting
confidence: 80%
“…Interestingly, EIMs at diagnosis have been also associated with a more severe course over time [ 17 ]. Similar results have been reported for pediatric-onset CD [ 18 ], suggesting that EIMs in children may have a worse prognosis than in adults and predict a more progressive disease course [ 15 , 19 , 20 ]. Aside from the younger age, the extension of disease and the degree of intestinal inflammation also seem to be associated with the risk of development of one or more EIMs [ 21 , 22 ].…”
Section: Extraintestinal Manifestations Of Ibdssupporting
confidence: 80%
“…In most patients, no extraintestinal manifestations (EIMs) were reported during treatment with biological agents (∼25% of patients receiving a TNF-α blocker had EIMs after initiation). This number is higher than that reported in other studies where the rate of all EIMs in patients with IBD was approximately 14% ( 46 ). The explanation for these results may be the longer follow-up of our patient cohort, as some of the patients were investigated almost 5 years after the initial entry in the registry.…”
Section: Discussioncontrasting
confidence: 66%
“…More recently, Jansson et al 19 reported that EIMs are associated with future disease severity in pediatric IBD, finding that EIMs in UC increased the risk of biological treatment and surgery, and EIMs in CD increased the relapse rate. These results support those in studies done with French and Swiss pediatric IBD patients.…”
Section: Discussionmentioning
confidence: 99%